(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2013)
The research aim is to identify and analize territorial approach of space flexibility in sinoman and biyada tradition in Karang Ampel Village Malang. The method used in this research is descriptive qualitative method by analyzing the results based on the results of the identification of characteristic and public-private function space changes. Sampling was done by purposive sampling criteria kinship closeness and differences availability of open space on observed objects. The results showed that the closeness of kinship ties have no effect on the formation of territorial expansion, but the differences in patterns of territory establishment as influenced by the availability of more open space (the back yard).